PENGARUH KECERDASAN SPRITUAL, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN PANTOLOAN - Junedi, Junedi (Katalogis, 2016)
The aim of this study is to analyze the influence of spritual quotient, work discipline, and work environment on the performance of official at the maritime and port authority of pantoloan. The research is explanative that shows the relevance of variables and involves 70 officials at the Maritime and Port Authority of Pantoloan who are selected as respondents through census technique sampling. Based on the result of multiple regression analysis tests, the study concludes that: 1) spiritual quotient, work discipline, and work environment simultaneously have positive impact on officials performance; 2) spiritual quotient partially has positive and significant impact on officials’ performance; 3) work discipline partially has positive and significant impact on officials’ performance; 4) work environment partially has positive and significant impact on officials’ performance.